Spaces of Radical Possibility: Designing for and from Intersectionality - Armaghan Ziaee (Trends in Higher Education)
This study examines the crucial role architecture plays in fostering inclusive and equitable experiences on college campuses, focusing on how physical spaces communicate implicit messages of access and belonging. Drawing on interdisciplinary feminist spatial justice frameworks and intersectional analysis, the research critiques traditional top-down design practices that may overlook the identity-based needs of diverse users. Through a case study approach, the paper highlights the disconnect between architectural intentions and lived experiences, illustrating how design choices can unintentionally reinforce social hierarchies. The study advocates for participatory architectural approaches that prioritize the voices and experiences of campus community members, promoting radical inclusivity in the design process. This research contributes to the ongoing discourse on integrating feminist and intersectional approaches into architectural education and practice, emphasizing the importance of creating more just and inclusive spaces.